Subsidiary shrine of the Someshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
View of the side shrine from the panchayatana (main shrine with four subsidiary shrines cardinal to the main temple) setup of the Someshwar Mahadev Temple. Not all these shrines have survived, except the shrines to the northwest and southeast of the main temple. This is the shrine to the southeast of the main temple. The four side shrines in the complex are single shrines dedicated to different deities, probably Vishnu, Ganesha, goddess, and Surya. Of the shikhara (superstructure) on these shrines, only a few aedicules of the base have survived.